BIMBINGAN DAN KONSELING ISLAM DENGAN TERAPI SILATURAHMI PADA SEORANG REMAJA YANG MENGALAMI DEPRESI (Jurusan Bimbingan dan Konseling Islam, 2013)
This study revealed the process of implementation of Islamic Guidance and Counseling with relationship therapy in an adolescent with depression. This study used qualitative methods with qualitative descriptive analysis. Data collection techniques used observation, interview and documentation to find the facts of the condition of a depressed teenager. Process of Islamic Guidance and Counseling with relationship therapy that counselors perform a variety of outreach activities, conversations and approaches with family and close friends counselee counselee to find out about the problems and conditions of the counselee . In addition , counselors also ask close friends help counselees to participate in providing assistance to the counselee to get out of the problems faced , because usually teens have a tendency to share feelings with peers . In this study concluded that the process of Islamic Guidance and Counseling with relationship therapy is quite successful with a percentage of 60 % , which these results can be seen from the change in attitude or behavior of the counselee who initially locked himself in the house into a venture out of the house.Keywords : Guidance and Counseling Islam , Gathering , Depression